2021
DOI: 10.1177/08850666211031813
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ABCDE Bundle Implementation in the Intensive Care Unit on Specific Patient Costs

Abstract: Objectives: To measure the impact of full versus partial ABCDE bundle implementation on specific cost centers and related resource utilization. Design: Retrospective cohort study. Setting: Two medical ICUs within Montefiore Health System (Bronx, NY). Patients: Four hundred and seventy-two mechanically ventilated patients admitted to the medical ICUs during a hospitalization which began and ended between January 1, 2013 and December 31, 2013. Interventions: The full (A)wakening, (B)reathing, (C)oordination, (D)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
(67 reference statements)
0
4
0
1
Order By: Relevance
“…Implementation of the ABCDE or ABCDEF bundle has been reported to improve mortality (4, 5, 32, 33), length of ICU or hospital stay (32, 34, 35), duration of mechanical ventilation (33, 34, 36), dosage of sedation (35), delirium or coma (4, 5, 36, 37), restraint-free care (5), hemodynamics (38), ICU readmissions (5), home discharge rates (5, 33), and costs (32, 34, 39). However, the long-term outcomes of implementing the ABCDEF bundle have not been studied to date.…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of the ABCDE or ABCDEF bundle has been reported to improve mortality (4, 5, 32, 33), length of ICU or hospital stay (32, 34, 35), duration of mechanical ventilation (33, 34, 36), dosage of sedation (35), delirium or coma (4, 5, 36, 37), restraint-free care (5), hemodynamics (38), ICU readmissions (5), home discharge rates (5, 33), and costs (32, 34, 39). However, the long-term outcomes of implementing the ABCDEF bundle have not been studied to date.…”
Section: Discussionmentioning
confidence: 99%
“…• 23 studies of care bundles, of which o 18 evaluated the ABCDE(F) bundle (Assess, prevent and manage pain, Both spontaneous awakening trials and spontaneous breathing trials, Choice of analgesia and sedation, Delirium assessment, prevention and management, Early mobility and exercise, Family engagement and empowerment) (Balas et al, 2013;Balas et al, 2022;Bardwell et al, 2020;Barnes-Daly et al, 2017;Barr et al, 2020;Boehm et al, 2020;Chen et al, 2021a;Collinsworth et al, 2021;Collinsworth et al, 2020;Costa et al, 2018;DeMellow et al, 2020;Hsieh et al, 2019;Lee et al, 2020;Loberg et al, 2022;Negro et al, 2022;Otusanya et al, 2021;Pun et al, 2019;Sosnowski et al, 2018). o Two evaluated a locally developed delirium prevention bundle (Bannon et al, 2018;Smith and Grami, 2016).…”
Section: In the Remaining 89 Implementation Studies We Identifiedmentioning
confidence: 99%
“…• The ICU day (n = 24, 27 %) (Balas et al, 2022;Bardwell et al, 2020;Barr et al, 2020;Boehm et al, 2020;Collinsworth et al, 2021;Collinsworth et al, 2020;DeMellow et al, 2020;Heim et al, 2019;Hsieh et al, 2019;Jablonski et al, 2017;Kamdar et al, 2013;Lee et al, 2020;Liu et al, 2016;Loberg et al, 2022;Ma et al, 2021;Negro et al, 2022;Otusanya et al, 2021;Pun et al, 2019;Smith and Grami, 2016;Sosnowski et al, 2018;Sutton et al, 2021;Tonna et al, 2021;Wessman et al, 2017;Zucco and Damirji, 2018). • The ICU stay (n = 8, 9 %) (Dalal et al, 2016;Dykes et al, 2017;Kodali et al, 2015;Loeslie et al, 2017;Nelson et al, 2006;Noome et al, 2017;Suen et al, 2021;Tonna et al, 2021).…”
Section: Tool Purpose and Objectivesunclassified
“…This bundle takes an integrated approach to managing pain (A element), sedation (C element), delirium (D element), mechanical ventilation (B element), and mobility (E element) in ICU patients, and engages patients and families in care processes (F element) (4)(5)(6)(7). Several studies have shown that this bundle significantly improves ICU patient care and outcomes, and reduces healthcare costs (4)(5)(6)(7)(8)(9)(10)(11). The bundle also has a dose-response effect on patient outcomes.…”
mentioning
confidence: 99%
“…Higher levels of bundle compliance are associated with greater reductions in the duration of mechanical ventilation, deep sedation, ICU delirium, and restraint use in ICU patients, along with greater decreases seen in ICU and hospital lengths of stay (LOS), ICU readmissions, hospital mortality, and skilled nursing facility discharges for ICU survivors (4, 5). Improved bundle performance is associated with significant and proportional reductions in ICU and hospital costs (6, 7, 12).…”
mentioning
confidence: 99%